(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the effect of a normal load on an infinite piecewise-homogeneous two-layer plate, when the materials of the upper and lower layers of the plate are elastic. The transverse displacement of points of the contact plane of a two-layer plate is determined, which satisfies the approximate equation obtained in [1], replacing only the viscoelastic operators with the elastic Lamé coefficients, respectively.